The Concept of Advertisement: An Islamic Perceptive - Begum, Azeema (Unisia, 2021)
There is a general perception regarding advertisement that advertising has a strong influence on consumer behavior. Advertisement has an imperative role in changing the social and cultural values of society. For convincing and getting consumer’s attention, advertising is considered the most successful and influential way of transforming information regarding new products. The paper argues the concept of advertisement in the light of Islamic Sharia’h.  We have found no evidence of any restriction for using advertisement as a promotional tool for products however; Islam has defined a certain set of laws that should be considered while making advertisements. Moreover, this paper also highlights some unethical issues of contemporary advertisement which are prohibited in Islam.